Prevalence of neurocognitive and perceived speech deficits in patients with head and neck cancer before treatment: Associations with demographic, behavioral, and disease‐related factors. Issue 2 (19th November 2021) - Piai, Vitória; Jansen, Femke; Dahlslätt, Kristoffer; Verdonck‐de Leeuw, Irma M.; Prins, Judith; Leemans, René; Terhaard, Chris H. J.; Langendijk, Johannes A.; Baatenburg de Jong, Robert J.; Smit, Johannes H.; Takes, Robert; P. C. Kessels, Roy; et al.
Abstract: Background: Neurocognition and speech, relevant domains in head and neck cancer (HNC), may be affected pretreatment. However, the prevalence of pretreatment deficits and their possible concurrent predictors are poorly understood. Methods: Using an HNC prospective cohort (Netherlands Quality of Life and Biomedical Cohort Study, N ≥ 444) with a cross‐sectional design, we investigated the estimated prevalence of pretreatment deficits and their relationship with selected demographic, behavioral, and disease‐related factors. Results: Using objective assessments, rates of moderate‐to‐severe neurocognitive deficit ranged between 4% and 8%. From patient‐reported outcomes, 6.5% of patients reported high levels of cognitive failures and 46.1% reported speech deficits. Patient‐reported speech functioning was worse in larynx compared to other subsites. Other nonspeech outcomes were unrelated to any variable. Patient‐reported neurocognitive and speech functioning were modestly correlated, especially in the larynx group. Conclusions: These findings indicate that a subgroup of patients with HNC shows pretreatment deficits, possibly accentuated in the case of larynx tumors.